Kinematic analysis of the back squat at different load intensities in powerlifters and weightlifters - Giustino, Valerio; Vicari, Domenico Savio Salvatore; Figlioli, Flavia; Gervasi, Marco; Fernández Peña, Eneko; Schifaudo, Naima; Tedesco, Mattia; Drid, Patrik; Paoli, Antonio; Battaglia, Giuseppe; Bianco, Antonino; Patti, Antonino (Frontiers in Sports and Active Living, 2024)
Introduction This study aimed to evaluate the angular kinematics of the hip, knee, ankle, and the linear kinematics of the barbell during the back squat (BS) at different load intensities in powerlifters and weightlifters. Methods Seventeen athletes were recruited (n = 14 powerlifters; n = 3 weightlifters). The 1-RM of the BS of each participant was calculated and, 1-week after, each participant was asked to perform 5 trials of the BS at different load intensities (i.e., 60%, 70%, 80%, 90%, 100%) of the 1-RM. An action camera recorded the execution of each BS trial in the sagittal plane and, afterward, the videos were analyzed by measuring the range of motion (ROM) of hip, knee, and ankle for the angular kinematics, and the timing, distances, speeds, and accelerations of the barbell for the linear kinematics. Results Regarding the angular kinematics, no significant differences were found in the parameters in the starting and ending positions among the 5 trials, while a significant decrease was found in the hip relative angle (p = 0.026) in the maximum flexion position as load intensity increased. Regarding the linear kinematics, a significant difference was found in the descent acceleration (p = 0.049) in the descent phase, while a significant difference was found in the ascent speed (p < .001) and vertical speed of ascent (p < .001) in the ascent phase, which decreased as load intensity increased. Discussion Our findings show that the angular and linear kinematics of BS change as load intensity increases.